2021
DOI: 10.5863/1551-6776-26.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of QTc Interval Effects of Antipsychotic Medications for Intensive Care Unit Delirium in Pediatric Patients

Abstract: OBJECTIVE Intensive care unit delirium is an increasingly recognized problem in pediatric patients. Controversy exists regarding the safety and efficacy of antipsychotic medications for this indication. The objective of this study was to determine the incidence of and risk factors for QTc interval prolongation in pediatric patients treated with antipsychotics for ICU delirium. METHODS Retrospective chart review of pediatric p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…It was found that patients with hypomagnesaemia had significantly longer PICU duration. A finding similar to the extension of ICU stay in patients with hypomagnesaemia was also found in Deshmukh et al, Chen et al, And Kumar et al study 22 . A relationship between hypomagnesaemia and other electrolyte disturbances was found in one third of the cases in this study.…”
Section: Discussionsupporting
confidence: 85%
“…It was found that patients with hypomagnesaemia had significantly longer PICU duration. A finding similar to the extension of ICU stay in patients with hypomagnesaemia was also found in Deshmukh et al, Chen et al, And Kumar et al study 22 . A relationship between hypomagnesaemia and other electrolyte disturbances was found in one third of the cases in this study.…”
Section: Discussionsupporting
confidence: 85%
“…Mild QTc prolongation has been reported in four patients (range: 450–454 ms) after risperidone initiation. 77 80 Two of the four patients also had documented electrolyte abnormalities and were receiving additional QTc prolonging medications at the time risperidone was initiated. No other adverse effects have been reported.…”
Section: Treatmentmentioning
confidence: 99%